Functional significance of the emotion-related late positive potential - Brown, Stephen B.; van Steenbergen, Henk; Band, Guido P.; de Rover, Mischa; Nieuwenhuis, Sander (Frontiers in Human Neuroscience, 2012)
The late positive potential (LPP) is an event-related potential component over visual cortical areas that is modulated by the emotional intensity of a stimulus. However, the functional significance of this neural modulation remains elusive. We conducted two experiments in which we studied the relation between LPP amplitude, subsequent perceptual sensitivity to a non-emotional stimulus (Experiment 1) and visual cortical excitability, as reflected by P1/N1 components evoked by this stimulus (Experiment 2). During the LPP modulation elicited by unpleasant stimuli, perceptual sensitivity and the P1 component were not affected. In contrast, we found some evidence for a decreased N1 amplitude during the LPP modulation, and consistent negative (but nonsignificant) across-subject correlations between the magnitudes of the LPP modulation and corresponding changes in d-prime or P1/N1 amplitude. The results provide preliminary evidence that the LPP reflects a global inhibition of ongoing activity in visual cortex, resulting in the selective survival of activity associated with the processing of the emotional stimulus.